Successful surgical repair in an older adult with supracardiac total anomalous pulmonary venous connection: A case report - Wang, Chunle; Xie, Xia; Zhuang, Huanwei; Huang, Zhonghua; Iroegbu, Chukwuemeka Daniel; Tang, Mi; Fan, Chengming; Yang, Jinfu (Frontiers in Cardiovascular Medicine, 2023)
Total anomalous pulmonary venous connection (TAPVC) is a rare, cyanotic and critical congenital heart disease where the entire left and right pulmonary veins fail to drain into the left atrium directly. Also, TAPVC-induced tissue hypoxia gradually worsens after birth. Thus, timely surgical repairs are recommended once diagnosed, particularly with pulmonary venous drainage obstruction(s). Nonetheless, in sporadic cases, patients with TAPVC survive to adulthood with no surgical treatment. Herein, we report a 46-year-old female with TAPVC, where the four pulmonary veins drain into to the innominate vein (IV) via the vertical vein. The patient developed palpitations and non-anginal chest pain following routine activities for over three months. The patient had a successful surgical correction with excellent postoperative recovery.